Abstract Expressionism at The Museum of Modern Art : Selections from the Collection - Ann Temkin; Nancy Grubb (NY; MoMA, 2010)
MoMA's unrivaled collection of Abstract Expressionist works More than 60 years have passed since Robert Coates, writing in the New Yorker in 1946, first used the term "Abstract Expressionism" to describe the richly colored canvases of Hans Hofmann. The name stuck, and over the years it has come to designate the paintings and sculptures of artists as different from one another as Jackson Pollock and Barnett Newman, Willem de Kooning and Mark Rothko, Lee Krasner and David Smith. The achievements of this generation put New York on the map as the center of the international art world, and constitute some of the twentieth century's greatest masterpieces. From the mid-1940s, under the aegis of Alfred H. Barr, Jr., works by then little-known American artists--including Pollock, de Kooning, Smith, Arshile Gorky and Adolph Gottlieb--began to enter the Museum's collection. These ambitious acquisition initiatives continued throughout the second half of the last century and produced a collection of Abstract Expressionist art the breadth and depth of which is unrivalled by any museum in the world. Supplemented by an essay by Ann Temkin, Chief Curator of Painting and Sculpture at MoMA, this volume celebrates the richness of the Museum's holdings of the paintings, sculptures, drawings, prints and photographs from this epochal moment in the history of art and of this institution.
English
Keywords: Expressionism; N4390-5098 Exhibitions